QUALITY 4.0 AND HR PRACTICES AT LIGHTHOUSES OF DIGITAL TRANSFORMATION - Drekovic, Edisa; Mihajlovic, Milan; Ahmatović, Amela (Poslovna ekonomija, 2023)
Quality 4.0 is a fascinating subject that interests both theoreticians and practitioners alike. As technology continues to advance, this topic is only going to become more distinguishing. This paper elucidates the concept of Quality 4.0, its advantages, and the crucial factors required for its implementation in companies. Importantly, it highlights the significance of having a competent workforce. The paper analyzes the human resource management practices that affect Quality 4.0 and identifies the most effective ones by studying companies that have succeeded in the process of digital transformation. By comparing the use cases of 9 "Lighthouses Network" companies of digital transformation in quality management and the HR practices they apply, the paper identifies the ways of working, and human resource management practices that lead to the effectiveness of Quality 4.0.